Question
upstudy study bank question image url

Use paseaf's triangle to sofve \( (2 x-1)^{5} \)

Ask by Hanson Rojas. in Ghana
Feb 25,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

\( (2x - 1)^5 = 32x^5 - 80x^4 + 80x^3 - 40x^2 + 10x - 1 \)

Solution

We can expand (2x – 1)^5 using the binomial theorem, which relies on Pascal’s triangle to give the binomial coefficients. For n = 5, the coefficients from Pascal’s triangle (the 6 numbers in the 5th row) are:   1 5 10 10 5 1 The binomial theorem states that   (a + b)^n = Σ from k = 0 to n of [nCk · a^(n–k) · b^k]. Here, let a = 2x and b = –1. Thus,   (2x – 1)^5 = Σ from k = 0 to 5 of [C(5, k) · (2x)^(5–k) · (–1)^k]. Now, let’s compute each term: 1. For k = 0:   Coefficient: C(5, 0) = 1   Term: 1 · (2x)^5 · (–1)^0 = 32x^5 2. For k = 1:   Coefficient: C(5, 1) = 5   Term: 5 · (2x)^4 · (–1)^1 = 5 · 16x^4 · (–1) = –80x^4 3. For k = 2:   Coefficient: C(5, 2) = 10   Term: 10 · (2x)^3 · (–1)^2 = 10 · 8x^3 · 1 = 80x^3 4. For k = 3:   Coefficient: C(5, 3) = 10   Term: 10 · (2x)^2 · (–1)^3 = 10 · 4x^2 · (–1) = –40x^2 5. For k = 4:   Coefficient: C(5, 4) = 5   Term: 5 · (2x)^1 · (–1)^4 = 5 · 2x · 1 = 10x 6. For k = 5:   Coefficient: C(5, 5) = 1   Term: 1 · (2x)^0 · (–1)^5 = 1 · 1 · (–1) = –1 Putting it all together, we have:   (2x – 1)^5 = 32x^5 – 80x^4 + 80x^3 – 40x^2 + 10x – 1

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Extra Insights

To expand \( (2x - 1)^{5} \) using Pascal's triangle, first identify the row corresponding to the exponent 5, which is the 5th row: \( 1, 5, 10, 10, 5, 1 \). Then, the general formula for the binomial expansion is \( (a + b)^{n} = \sum_{k=0}^{n} \binom{n}{k} a^{n-k} b^{k} \). For \( (2x - 1)^{5} \): - \( a = 2x \) - \( b = -1 \) - \( n = 5 \) Expanding it gives us: \[ \begin{align*} (2x - 1)^{5} &= \binom{5}{0} (2x)^{5} (-1)^{0} + \binom{5}{1} (2x)^{4} (-1)^{1} + \binom{5}{2} (2x)^{3} (-1)^{2} \\ &\quad + \binom{5}{3} (2x)^{2} (-1)^{3} + \binom{5}{4} (2x)^{1} (-1)^{4} + \binom{5}{5} (2x)^{0} (-1)^{5} \\ &= 1 \cdot (2x)^{5} - 5 \cdot (2x)^{4} + 10 \cdot (2x)^{3} - 10 \cdot (2x)^{2} + 5 \cdot (2x)^{1} - 1 \cdot (1) \\ &= 32x^{5} - 80x^{4} + 80x^{3} - 40x^{2} + 10x - 1. \end{align*} \] So, the expanded form is \( 32x^{5} - 80x^{4} + 80x^{3} - 40x^{2} + 10x - 1 \).

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy